Hypertension and patients with acute coronary syndrome: Putting blood pressure levels into perspective. Issue 8 (12th July 2019) - Konstantinou, Konstantinos; Tsioufis, Costas; Koumelli, Areti; Mantzouranis, Manos; Kasiakogias, Alexandros; Doumas, Michalis; Tousoulis, Dimitris
Abstract: Arterial hypertension is a well‐established cardiovascular risk factor, and blood pressure (BP) control has largely improved the prognosis of hypertensive patients. A number of studies have assessed the role of BP levels in the prognosis of patients with acute coronary syndromes. Pathophysiologic links of hypertension to acute myocardial infarction (MI) include endothelial dysfunction, autonomic nervous system dysregulation, impaired vasoreactivity, and a genetic substrate. A history of hypertension is highly prevalent among patients presenting with MI, and some, but not all, studies have associated it with a worse prognosis. Some data support that low levels of admission and in‐hospital BP may indicate an increased risk for subsequent events. Risk scores used in patients with MI have, therefore, included BP levels and a history of hypertension in their variables. Of note, good long‐term BP control, ideally initiated prior to discharge, should be pursued in order to improve secondary prevention.